2013
DOI: 10.1074/jbc.m113.492314
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Hepatitis C Virus (HCV)-induced Osteopontin and Its Role in Epithelial to Mesenchymal Transition of Hepatocytes

Abstract: Background:The mechanism underlying HCV-induced OPN remains elusive. Results: HCV-induced Ca 2ϩ signaling, oxidative stress, and activation of AP-1 and Sp1 play a critical role in OPN activation. Conclusion: OPN plays important roles in EMT and cell migration induced by HCV through the activation of Akt, GSK-3␤, and ␤-catenin. Significance: Our findings provide a novel implication of OPN in HCV-induced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 63 publications
2
46
1
Order By: Relevance
“…The presence of HCV in these cells and the corresponding supernatants was determined as described previously (33). The cell-free virus was propagated in Huh7.5 cell culture as described previously (32)(33)(34). The expression of HCV protein in HCV-infected cells was analyzed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of HCV in these cells and the corresponding supernatants was determined as described previously (33). The cell-free virus was propagated in Huh7.5 cell culture as described previously (32)(33)(34). The expression of HCV protein in HCV-infected cells was analyzed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of HCV protein in HCV-infected cells was analyzed by Western blotting. The HCV cell culture supernatant was collected at appropriate time points and used to infect naïve Huh7.5 cells at a multiplicity of infection of 1 for 5-6 h at 37°C and 5% CO 2 (32,33). The viral titer in the cell culture supernatant was expressed as focus forming units per milliliter, which was determined by the average number of HCV-NS5A-positive foci detected at the highest dilutions, as described previously (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58] Reports that Sp1 plays a role in liver injury are more anecdotal. [59][60][61] To confirm the role of these four factors, we performed ChIP-seq on liver samples 1 and 14 days after ligation. Increased Jun binding occurred at both time points.…”
Section: Resultsmentioning
confidence: 99%
“…c-Kit promoter activity is known to be upregulated by Sp1 (27). In previous studies, we and others have reported that HCV core enhances Sp1 promoter activity (28,29), which may be a mechanism by which c-Kit expression is enhanced in the presence of HCV.…”
Section: Resultsmentioning
confidence: 99%